Development of a Novel Quantum Dots and Graphene Oxide Based FRET Assay for Rapid Detection of invA Gene of Salmonella - Guo, Jiubiao; Chan, Edward W. C.; Chen, Sheng; Zeng, Zhenling (Frontiers in Microbiology, 2017)
A novel, rapid and simple fluorescence resonance energy transfer (FRET) based Salmonella specific gene, invA, detection system was developed, in which quantum dots (QDs) and graphene oxide (GO) worked as fluorescent donor and quencher respectively. By measuring the fluorescence intensity signal, the Salmonella specific invA gene could be sensitively and specifically detected with a limit of detection (LOD) of ~4 nM of the invA gene in 20min. The developed system has the potential to be used for Salmonella detection in food and environmental samples and further developed into a platform for detection of other bacterial pathogens.